Pengembangan E-Modul Berbasis Chemo-Entrepreneurship (CEP) pada Materi Koloid untuk Meningkatkan Hasil Belajar dan Minat Berwirausaha Peserta Didik Kelas XI - Ramlah, Ramlah; Aulia, Army; Sugiarti, Sugiarti (Program Pasca Sarjana UNM, 2023)
This research is a Chemo-Entrepreneurship (CEP)-based E-Module development research on colloidal material which aims to improve learning outcomes and interest in entrepreneurship for class XI students of SMA Negeri 1 Manokwari. This e-module was developed using the Lee & Owens development model which consists of five main stages, namely: analysis, design, development, implementation, evaluation. The research subjects were 54 students in class XI IPA 1 and IPA 2. The sampling technique used purposive sampling. Data collection techniques used instruments: (1) teacher assessment questionnaires, (2) student response questionnaires, (3) interest in entrepreneurship questionnaires and (4) learning achievement tests. The results of this study indicate that this E-Module is